The Quality of Randomized Controlled Trial in Cochrane Kidney and Transplant Group - Hanieh Salehi-Pourmehr; Ali Mostafaei; Amir Mehdizadeh; Sakineh Hajebrahimi; Leila Hosseini; Zahra Sheikhalipour; Nasrin Abolhasanpour (Journal of Urological Surgery)

(untitled)
Objective:Misconduct is one of the important issues in research integrity. Cochrane systematic reviews are known for their best level of evidence. Since kidney failure is a major public health problem worldwide, the Cochrane Library provides a robust and reliable database to upgrade medical knowledge and make the best medical decisions. Therefore, this study aimed to assess the quality of randomized controlled trials (RCTs) that are included in the Cochrane systematic reviews of kidney and transplant groups.Materials and Methods:This analytic cross-sectional study was conducted on systematic reviews of kidney and transplant group of Cochrane reviews. All types of biases in the understudied RCTs or quasi-RCTs of these systematic reviews were evaluated using the Cochrane appraisal checklist. The types of biases in included studies were also separated and stratified. Descriptive statistics were used for data analysis using the Statistical Package for the Social Sciences 16.Results:A total of 267 systematic reviews and their understudied 3213 RCTs were evaluated. In the kidney and transplant group, the highest risk of bias was seen in allocation concealment bias, whereas the most common bias was unclear allocation concealment (selection bias). From 2008 to 2009, high random sequence generation bias has dramatically increased, and after decreasing, the gradual growth has been continuing over time. Furthermore, the low detection bias has reduced surprisingly in 2011 then decreased in 2012-2013.Conclusion:Regarding high risks of performance and random sequence generation biases in understudied RCTs, critical structure deficiencies were obvious. Therefore, observing integrity principles to prevent research misconduct is recommended.